Beyond Val30Met transthyretin (TTR): variants associated with age-at-onset in hereditary ATTRv amyloidosis. (3rd April 2021) - Alves-Ferreira, Miguel; Azevedo, Ana; Coelho, Teresa; Santos, Diana; Sequeiros, Jorge; Alonso, Isabel; Sousa, Alda; Lemos, Carolina
Abstract: Objectives: V30M in transthyretin ( TTR ) gene is causative for hereditary ATTRv amyloidosis (familial amyloid polyneuropathy). ATTRv amyloidosis shows a wide variation in age-at-onset (AO) between clusters, families, and among generations. We aim at identifying genetic modifiers of disease onset that may contribute to this variability in Portuguese patients by identifying other variants in TTR locus, beyond the ATTRv amyloidosis causing variant that could play a regulatory role in its expression level. Methods: We analysed DNA samples of 330 ATTRV30M carriers (299 patients, 31 aged-asymptomatic carriers aged >40 years) from 120 families currently under follow-up. A generalised estimating equation analysis (GEE) was used to take into account non-independency of AO between relatives. An intensive in silico analysis was performed in order to understand a possible regulation of gene expression. Results: We found 11 rare variants in the promoter, coding and intron/exon boundaries of the TTR gene associated with the onset of symptoms before and after age 40 years, namely 2 novel ones and a tandem CA-dinucleotide repeat. Furthermore, of the 4 common variants found, one was significantly associated with AO and may influence the constitutive splicing of TTR pre-mRNA. The seven ATTRV30M/V30M homozygous do not carry any of the variants identified in this study, including the common ones. In silico analysis disclosed significant alterations in the mechanism of splicing, transcription factors and miRNAs binding. Conclusions: Variants within the promoter region may modify disease expressivity and variants in the 3'UTR can impact the efficacy of novel therapeutic interventions. Importantly, the putative mechanisms of regulation of gene expression within the TTR gene deserve to be better explored, in order to be used in the future as potential therapeutical targets.